2018
DOI: 10.1097/phm.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Scoring System for the Prediction of Functional Deterioration, Institutionalization, and Mortality Among Medicare Beneficiaries

Abstract: A risk scoring system predicting Medicare beneficiaries' risk of functional deterioration, institutionalization, and mortality based on demographic and clinical indicators may feasibly be developed with implications for healthcare delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Older populations experience some level of difficulties in performing IADL with deterioration of physical and cognitive functioning [ 4 ]. Increased dependence in older adults is associated with hospitalization and admission to long-term care facilities, leading to increase in morbidity and mortality from diseases along with a decrease in quality of life [ 5 , 6 ]. Increased dependence in older adults also increases social burden due to increased care needs and medical costs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older populations experience some level of difficulties in performing IADL with deterioration of physical and cognitive functioning [ 4 ]. Increased dependence in older adults is associated with hospitalization and admission to long-term care facilities, leading to increase in morbidity and mortality from diseases along with a decrease in quality of life [ 5 , 6 ]. Increased dependence in older adults also increases social burden due to increased care needs and medical costs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been widely reported that various physiological, psychological and behavioural factors play roles in explaining the possible pathways through which cognitive function affected the health and mortality of OAs. 10,11 From the physiological perspective, cognitive impairment is associated with physical disability, 12 institutionalisation, 13 hospitalisations 14 and mortality among community-dwelling and hospitalised OAs. 15 Villarreal 16 indicated that the effects of socio-demographic factors on the decline of functional status may be direct or indirect via physiological processes.…”
Section: Introductionmentioning
confidence: 99%